Overnight Social Isolation in Pigs Decreases Salivary Cortisol but Does Not Impair Spatial Learning and Memory or Performance in a Decision-Making Task - van der Staay, F. Josef; Schoonderwoerd, Annelieke J.; Stadhouders, Bo; Nordquist, Rebecca E. (Frontiers in Veterinary Science, 2016)
Pigs in modern farming practice may be exposed to a number of stressors, including social stressors such as mixing or isolation. This may potentially affect both cognitive abilities and stress physiology of the animals. We tested the hypothesis that overnight social isolation in pigs impairs performance in a cognitive Holeboard (HB) task (Experiment 1) and the Pig Gambling Task (PGT) (Experiment 2), a decision making task inspired by the Iowa Gambling Task. In addition, we tested the effect of overnight social isolation on salivary cortisol levels. A within-subjects approach was used in which performance in the two behavioral tasks and cortisol levels were first determined during normal social housing, followed by performance and cortisol levels after experiencing stress induced by overnight social isolation. A total of nineteen female pigs with a birthweight closest to their respective litter average was selected from 10 different litters and placed in two pens after weaning. Following habituation, pigs were trained in the HB task, starting at 10 weeks of age. Then, the pigs were isolated overnight, five individuals per night, at 15, 16 and 17 weeks of age. Between these three isolations, social housing and training in the HB continued. Starting 6 weeks after the end of the HB experiment, at approximately 23 weeks of age, the pigs were trained in the PGT. The effects of overnight social isolation on performance in this task were assessed once, when the pigs were 25 weeks old. Salivary cortisol was measured from samples collected 15 minutes after the start of isolation and at the end of the isolation period, and compared to baseline values collected before the start of social isolation. Our results did not confirm the hypothesis that isolation impaired HB performance and decision making in the PGT. Unexpectedly, overnight social isolation decreased cortisol levels below baseline values, an effect that was not associated with changes in performance of the behavioral tasks. We hypothesized that the housing and testing conditions may have prepared the animals to cope efficiently with stress.